Ebook quality - Millán, José-Antonio (Anuario ThinkEPI, 2015)
The poor orthotypographical quality of many ebooks is not intrinsic to the characteristics of the epub format, but the lack of professionalism in their production. The resulting bad products may be responsible for the scant development of this kind of book distribution.